When Ecological Analysis Reveals Hidden Human Dimensions: Building on Long-Term Community Participation to Enable a Conservation Translocation of Mountain Bongo in Kenya - Sheppard, Donna J.; Brichieri-Colombi, Typhenn A.; Stark, Danica J.; Lambrechts, Christian; Moehrenschlager, Axel; McPherson, Jana M. (Frontiers in Conservation Science, 2022)
Conservation translocations have traditionally focused on ecological aspects of translocations while overlooking or underestimating the importance of human dimensions. Here we present a feasibility analysis for a conservation translocation that up front took a holistic approach by investigating both ecological and socio-economic suitability of reinforcing mountain bongo in Eburu National Forest, Kenya. From 2018-2019, we set up 50 cameras to detect mountain bongo and searched for secondary signs in a grid overlaying Eburu. We also conducted surveys with the heads of 200 households surrounding the forest and interviewed 200 students to understand local perceptions of and interactions with Eburu Forest and their desire for a mountain bongo translocation. We used data from camera trapping and secondary signs in a MaxEnt model to determine the amount and location of available habitat for a bongo conservation translocation. Camera traps recorded only 5 bongo events in the 2-year study, and MaxEnt models revealed that these antelopes were relegated to approximately 2.5 km of available habitat. Socio-economic surveys indicating overwhelming local support for the conservation of bongo and their habitat, and yet our camera traps uncovered threatening illicit activities that could jeopardize both bongo survival and any attempt at boosting the remnant population with captive-bred individuals. We report how we built on long-term community and stakeholder engagement to mitigate these threats and provide concrete recommendations for how to proceed with a conservation translocation in terms of both the biological aspects and continued efforts to integrate socio-economic needs and community engagement.